Research Skills for Information Management: Uses of Mobile Devices in Research Training - Erika Juliana Estrada Villa; Victoria I. Marín; Jesús Salinas (MDPI AG, 2021)
Although we live in a knowledge society, instruction in research is still given traditionally. Mobile devices are present in learning processes, but their possibilities for research have not been broadly explored. This paper explores the research skills that could be supported using information communication technology through mobile devices. We start from theoretical frameworks related to andragogy, knowledge management, the technology acceptance model, and mobile learning. As a case study, 20 Colombian virtual education students studying for master's degrees answered a questionnaire. The results revealed an acceptance of mobile device use in education and a tendency to use apps for information management. These results suggest the need to change the teaching process and design a strategy for the inclusion of mobile learning in research. The use of mobile learning can enhance research training processes framed in the emergent mode of knowledge or context-centric research, especially in virtual higher education.